Genetic analysis of Iranian autosomal dominant polycystic kidney disease: new insight to haplotype analysis - Entezam, M; Khatami, M R; Saddadi, F; Ayati, M; Roozbeh, J; Saghafi, H; Keramatipour, M (Cellular and Molecular Biology, 2016)
Autosomal Dominant Polycystic Kidney Disease (ADPKD) caused by mutations in two PKD1 and PKD2 genes. Due to the complexity of the PKD1 gene, its direct mutation screening is an expensive and time-consuming procedure. Pedigree-based haplotype analysis is a useful indirect approach to identify the responsible gene in families with multiple affected individuals, before direct mutation analysis. Here, we applied this approach to investigate 15 appropriate unrelated ADPKD families, selected from 25 families, who referred for genetic counseling. Four polymorphic microsatellite markers were selected around each PKD1 and PKD2 loci. In addition, by investigating the genomic regions, two novel flanking tetranucleotide STR markers were identified. Haplotype analysis and calculating Lod score confirmed linkage to PKD1 in 9 families (60%) and to PKD2 in 2 families (13%). Linkage to both loci was excluded in one family (6.6%). In 2 families (13%) the Lod scores were inconclusive. Causative mutation was identified successfully by direct analysis in two families with confirmed linkage, one to PKD1 and another to PKD2 locus. The study showed that determining the causative locus prior to direct mutation analysis is an efficient strategy to reduce the resources required for genetic analysis of ADPKD families. This is more prominent in PKD2-linked families. Selection of suitable markers, and appropriate PCR multiplexing strategy, using fluorescent labeled primers and 3 primer system, will also add value to this approach.